Penggunaan Qirâ`at dalam Tafsir Ma’âni Al-Qur`ân Karya Al-Farra` (761-822) - Rahmat Nurdin (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2017)
Al-Qur`an and qirâ`at are two different things, but both are complementary, where the terms of the al-Qur`an can’t be separated from qirâ`at aspect for understanding al-Qur`an itself as a language is being read or reading. In some book of commentary that there can be seen a variety of qirâ`at the interpreter quotes from priests qirâ`at. The book Ma'âni al-Qur`ân by al-Farra` (761-822) is one book of commentary patterned linguistic use some variety qirâ`at in explaining the meaning of the verse of al-Quran. As the name implies, this book is more dominant explain the meaning contained in Al'Qur`an especially the explanation of i'rab al-Qur`an.